The Effect Of Islamic Social Reporting And Profitability On Assets On Fiscal Aggressiveness With An Independent Commissioner As A Moderator Variable - Dien Sefty Framitha; Nana Umdiana; Elsa Amelia Ristia Depi (JAK (Jurnal Akuntansi) Kajian Ilmiah Akuntansi, 2023)
This study aims to examine the influence of Islamic Social Reporting and Return On Assets On Tax Agressiveness With Independent Commissioner As a Moderation Variable. This study was conducted on company listed in Jakarta Islamic index during the 2015-2019. The determination of sample by using purporsive sampling method. The number of samples of this study were 11 companies for 5 years with a total of 55 data samples. The data analysis method using multiple linear regression analysis method and moderate regression analysis (MRA) with the help of IBM SPSS 25 software. The results showed that Islamic Social Reporting And Return On Assets does not affect the tax aggressiveness. Independent Commissioner can moderate the effects of Islamic Social Reporting on tax aggressiveness. However, Independent Commissioner is not able moderate the effects of Return On Assets on tax aggressiveness.